Analisis Kebutuhan E-Modul Multimedia untuk Melatih Kemampuan Berpikir Kronologis pada Mata Pelajaran Sejarah Kelas XI Fase F di SMK N 9 Padang - Lumbanbatu, Yente Kristina; Yefterson, Ridho Bayu (Jurnal Kronologi, 2024)
This reasearch aims to analyze the needs for multimedia e-modules to train chronological thinking skills in History subjects for Grade XI Phase F at SMK N 9 Padang. The analysis is based on interviews conducted with students and teachers to identify challenges and preferences in learning and teaching History. The findings suggest that students face difficulties in understanding historical chronology, while teachers encounter challenges in presenting historical material effectively. The implication is the necessity for developing e-modules that cater to students' preferences for visual and interactive learning, while also supporting teachers in facilitating effective teaching strategies. By addressing these needs, e-modules can enhance the learning experience and improve students' chronological thinking skills in History.